2001
DOI: 10.1001/jama.285.14.1856
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Treatment of Chronic Primary Insomnia

Abstract: Our results suggest that CBT represents a viable intervention for primary sleep-maintenance insomnia. This treatment leads to clinically significant sleep improvements within 6 weeks and these improvements appear to endure through 6 months of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
339
5
14

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 567 publications
(375 citation statements)
references
References 37 publications
17
339
5
14
Order By: Relevance
“…24 Unfortunately, broader adoption of CBTi has been hindered by several factors, including the relatively limited number of clinicians trained to provide it and the fact that the length of traditional protocols (6-10 sessions) is not well-matched to the resources available in primary care settings where the majority of insomnia cases are seen. [25][26][27] However, Manber and colleagues have described the successful training of mental health clinicians without sleep specialization to deliver CBTi in the VA healthcare system. 28 In response to this, shortened protocols (i.e., ≤ 4 sessions) have been developed, and research has shown them to be efficacious and effective in treating insomnia in adults of all ages (see McCrae, 29 Buysse,30 or Edinger and Sampson, 31 for review).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…24 Unfortunately, broader adoption of CBTi has been hindered by several factors, including the relatively limited number of clinicians trained to provide it and the fact that the length of traditional protocols (6-10 sessions) is not well-matched to the resources available in primary care settings where the majority of insomnia cases are seen. [25][26][27] However, Manber and colleagues have described the successful training of mental health clinicians without sleep specialization to deliver CBTi in the VA healthcare system. 28 In response to this, shortened protocols (i.e., ≤ 4 sessions) have been developed, and research has shown them to be efficacious and effective in treating insomnia in adults of all ages (see McCrae, 29 Buysse,30 or Edinger and Sampson, 31 for review).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Cognitive-behavior therapy for insomnia (CBT-I), a multi-component treatment package that includes stimulus control, sleep restriction, relaxation exercises, and cognitive restructuring techniques, has demonstrated efficacy for the treatment of insomnia (e.g., (2)(3)(4)(5)). Meta-analyses have reported large effect sizes for reducing sleep onset latency and improving sleep quality and medium effect sizes for reducing wake time after sleep onset and increasing total sleep time (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment outcome studies were inconsistent in reporting attrition, thus making it difficult to estimate the rate of dropouts. The recommendations outlined in the CONSORT statement (11) have improved the reporting of patient flow in randomized clinical trials (RCTs) and more recent RCTs using individual or group CBT-I for primary insomnia have revealed very low rates of dropout for participants in the CBT-I condition, ranging from 0% to 8% (2)(3)(4)(5). However, RCTs typically recruit homogenous samples, most commonly limited to patients with primary insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…El terapeuta se vale de una serie de téc-nicas dirigidas a lograr la relajación mental y física mediante relajación muscular progresiva, terapia de control de estímulos 15 , terapia de intención paradójica, biofeedback asistido por mecanismos auditivos o visuales, respiración diafragmática, imaginación guiada por sugerencias, parada del pensamiento, restricción del sueño, etc... 16 . El paciente debe modificar la conducta limitando el tiempo de permanencia en la cama, estableciendo horarios (levantarse y acostarse a la misma hora), evitando siestas y cuidando el entorno ambiental del sueño.…”
Section: La American Academy Of Sleep Medicineunclassified